OPTIMALISASI BIAYA DISTRIBUSI KAIN MENTAH DI PT PQR MENGGUNAKAN METODE VAM (VOGELS APPROXIMATION METHOD) DAN LINGO - Salma Rifaza Wahyu; Ana Rohima; Kristina Fitri Handayani; Muchammad Fauzi (Jurnal Bayesian : Jurnal Ilmiah Statistika dan Ekonometrika, 2021)
Transportation is one of the most important things in distribution. One of them is PT. PQR distributes its products to a variety of different locations. PT. PQR is a textile factory located in 3 different places. PT. PQR manufactures a wide range of fabrics, manufacturing fabricated garments, clothing and socks. The company supplies fabric needs from both local and interlocal consumers. Therefore, careful planning is needed so that the flow of shipping does not go back and forth and is expected to minimize costs or costs. The method used to support the decision to be made is the VAM (Vogels Approximation Method). Researchers also use another method, lingo software as a comparison. The results obtained from this study will be used as a reference in decision making to distribute raw fabric to several different locations. Of course, the decision taken in accordance with expectations, namely the distribution of raw fabric at a small cost or as optimal as possible. The results and handling of Transportation using theVogels Approximation Method (VAM) are quite effective in its usefulness as a calculation of transportation costs in PT. PQR with a result of Rp 58,160,000, which is the same result as the results of LINGO software which is a programming application optimization model where the results obtained are optimal.